Production of Processed Cheese Using Lipase-Catalyzed Transesterified Palm Kernel Olein and Anhydrous Milk Fat Mixtures - Mohamed Ismail, Mariam (1999)
In recent years, lipase-catalyzed transesterification has received considerable attention from the fats and oils industry due to its potential to modify the physical and chemical properties of edible fats and oils. In this study, enzymatic transesterification of three different ratios of palm kernel olein (PKO) and anhydrous milk fat (AMF) was carried out using immobilized lipase from Rhizomucor miehei (Lipozyme 1M 60) to modify their chemical and physical properties, such that they can be used in the production of processed cheese. After transesterification for 8 hours, there were either increases or decreases in the concentrations of several existing triglycerides (TG) of the reaction mixtures and, in some cases, the formation of new peaks. The results also showed that increasing the reaction time, increased the % free fatty acid (FF A) between 1 to 2%.of free fatty acids, declined after the transesterification process. The solid fat content (SFC) decreased with respect to the control samples. At 40°C, the PKO:AMF (7:3) transesterified fat mixture was completely melted, making it a potential candidate in the formulation of processed cheese. Thermal profiles showed that the original peaks of the transesterified mixtures have either shifted or completely changed and some new peaks were also formed. It was also found that the transesterified fat mixtures were in the β form, compared to a predominantly β form before transesterification. After the preparation of experimental processed cheese, several chemical and physical analyses of this final product were carried out. The results showed that the experimental processed cheese had a satisfactory aroma and texture compared to the commercial sample. It also recorded a high total solid content and a low amount of moisture, with a good workability and overall general behaviour at cool, ambient, and elevated temperatures.Sensory evaluation and texture analysis studies were also conducted on the final product. The experimental processed cheese samples achieved an acceptable response from the panelists, where there was no significant difference between the samples in terms of colour and texture. The texture profiles indicated that the experimental processed cheese samples exhibited close texture profiles compared to their counterpart commercial sample.